Nickel‐Catalyzed Electroreductive Syntheses of Triphenylenes Using ortho‐Dihalobenzene‐Derived Benzynes. Issue 19 (26th July 2022) - Li, Zhao‐Ming; Shuai, Bin; Ma, Cong; Fang, Ping; Mei, Tian‐Sheng
Comprehensive Summary: Electrochemical nickel‐catalyzed syntheses of triphenylenes by a) reductive trimerization of ortho ‐dibromobenzenes or ortho ‐bromoarylsulfurofluoridates, or b) reductive cross‐coupling of ortho ‐dibromobenzenes to 2, 2'‐diiodobiphenyls, are described. The former provides a practical means for the construction of triphenylene derivatives in up to 87% isolated yield at room temperature. For 1, 2‐dihalo‐3‐methylbenzenes and related ortho‐ trisubstituted substrates, trimerizations proceed with high substrate‐controlled regioselectivity for the non‐ C 3h symmetric triphenylene isomer. Abstract :